2021
DOI: 10.1371/journal.pone.0256819
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of Phlebotomus argentipes: Vector of Leishmania donovani in Sri Lanka

Abstract: Phlebotomus argentipes is the vector of Leishmania donovani which causes the disease leishmaniasis, a neglected tropical disease and a growing health problem in Sri Lanka. A proper understanding of the population genetic structure of sand fly vectors is considered important prior to planning and implementation of a successful vector control program. Thus, the present study was conducted to determine the population genetic structure of sand fly vectors in Sri Lanka. Two mitochondrial genes namely Cytochrome c o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Previous studies conducted in Sri Lanka have also reported Ph. argentipes as the predominant species of sand flies [ 20 , 33 , 34 ]. However, this current study is significant in that it demonstrates the widespread presence of Ph.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies conducted in Sri Lanka have also reported Ph. argentipes as the predominant species of sand flies [ 20 , 33 , 34 ]. However, this current study is significant in that it demonstrates the widespread presence of Ph.…”
Section: Discussionmentioning
confidence: 99%
“…Among the factors investigated, wind speed has the potential to influence the dynamic behavior of sand flies, particularly in terms of gene flow between populations without geographical barriers. This gene flow can facilitate the transfer of genes that promote sand fly survival, such as insecticide resistance genes [ 34 ], which can have negative implications for vector control programs. However, the present study did not find any relationship between sand fly density and wind speed.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Phlebotomus argentipes Annandale and Brunetti (1908), one of the 1060 sandfly species globally, emerges as a main vector for VL and CL in Sri Lanka and India [7]. In Sri Lanka, P. argentipes is currently recognized as a species complex, and its distribution has been documented across all three climatic zones in the country [10,11]. The distribution pattern of P. argentipes over the country highlights the epidemic risk of the disease, emphasizing the significance of vector control in effective disease management [8].…”
Section: Introductionmentioning
confidence: 99%
“…The extensive utilization of insecticides like DDT and malathion, had been identified as effective control of other vectors, also it indirectly influences the development of insecticide-resistant P. argentipes populations [12]. As the P. argentipes vector species is well established in arid regions where malaria is prevalent, non-targeted control strategies are likely to have an effect on the development of insecticide resistance in these communities [11]. However, as a consequence of these factors, changes in the genetic composition of the P. argentipes community in Sri Lanka led to an increase in their genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation